Combination of spectroscopic ellipsometry and spectroscopic reflectometry with including light scattering in the optical characterization of randomly rough silicon surfaces covered by native oxide layers. (19th September 2019) - Ohlídal, Ivan; Vohánka, Jiří; Čermák, Martin; Franta, Daniel
Abstract: A combined method of spectroscopic ellipsometry and spectroscopic reflectometry is employed for the optical characterization of randomly rough surfaces of silicon single crystal covered with very thin native oxide layers within spectral range 197–1240 nm (1.0–6.3 eV). It is shown that random roughness of the samples of this system exhibits a wide interval of spatial frequencies so that the Rayleigh–Rice theory, scalar diffraction theory for coherent light and scalar diffraction theory with including light scattering must be used to achieve good fits of experimental data. The ellipsometric data are compatible with the Rayleigh–Rice theory within the entire spectral range while the reflectometric data must be processed separately within two sub-ranges using two different theoretical approaches. In one of the sub-ranges the combination of Rayleigh–Rice theory and scalar diffraction theory for coherent light is utilized for obtaining good fits of the corresponding experimental data of reflectance. Within the latter sub-range the scalar diffraction theory including the influence of light scattering on reflectance enables us to achieve good fits. Further, it is shown that using this combined method the values of basic roughness parameters, i.e. the rms values of heights, autocorrelation lengths and rms values of slopes of roughness irregularities, can be determined together with thickness values of the native oxide layers. A comparison of the results achieved optically with those determined by atomic force microscopy is performed. The assessment of efficiency of spectroscopic ellipsometry and spectroscopic reflectometry in characterizing random roughness with the wide interval of spatial frequencies is also presented.